LEFT VENTRICLE UNLOADING BY PERCUTANEOUS TRANSFEMORAL TRANSSEPTAL CANNULATION OF LEFT ATRIUM IN PATIENTS BRIDGED TO HEART TRANSPLANTATION WITH PERIPHERAL VENO-ARTERIAL EXTRACORPOREAL MEMBRANE OXYGENATION - V. N. Poptsov; E. A. Spirina; V. V. Slobodjannik; V. M. Zakharevich; O. A. Eremeeva; S. A. Masiutin (Вестник трансплантологии и искусственных органов, 2014)
Aim. Peripheral VA ECMO is effective method of circulatory support in heart transplant candidates with life th- reatening CHF. However this type of extracorporeal life support may be complicated by pulmonary congestion (“white lung”) as a result of left ventricle (LV) dilatation and volume overload. Difference approach proposed for LV unloading following VA ECMO circulatory support. We report our experience of LV unloading by percutaneous introduced of supplement drainage cannula in the left atrium (LA ) through the femoral vena and interatrial septum. Material and methods. In this study was included 33 heart transplant candidates (6/27 F/M, age 46.2 ± 3.7 yrs) on peripheral VA ECMO support. For LV unloading we used supplement standard venous ECMO-cannula (15–19 F) percutaneous introduced in LA through the femoral vena of conterlateral leg and connected to the venous line of ECMO circuit. Results. To 20 (60.6%) from 33 patients needed of early (n = 10) or delayed (n = 10) LA drainage. After beginning of LV drainage we noted of significant (p < 0.05) decreasing of PAWP from 31 ± 3 to 14 ± 3 mm Hg and resolution of pulmonary edema. Mean blood flow on LA cannula was 1.5 ± 0.2 l/min. To 18 (90%) from 20 patients was successfully bridged to heart transplantation. Duration VA ECMO before OHT was 8.6 ± 1.7 days. 16 (88.9%) recipients were discharged from hospital. Conclusion. Active LA drainage is as effective tool of LV un- loading and protection of pulmonary congestion and edema in patients bridged to heart transplantation by peripheral VA ECMO.